Application of digital twin model based industrial internet - Bin LIU; Yunyong ZHANG (Dianxin kexue)
Industrial internet is an important engine for manufacturing enterprises to provide intelligent products and services in China.From manufacturing enterprises’ point of view,the definition and data sources of industrial internet were introduced,and the five-layer function architecture of industrial internet was proposed.The industrial data analysis model represented by digital twin played a crucial role in developing industrial internet for manufacturing enterprises,whose definition,characteristics,key technologies and applications in the whole product lifecycle were elaborated.Finally,the problems and solutions of carrying forward industrial internet in China were addressed.